2018
DOI: 10.1007/s11356-018-3041-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the vertical migration of different-sized Microcystis colonies: coupling turbulent mixing and buoyancy regulation

Abstract: Exceptional vertical migration ability provides the cyanobacterium Microcystis with competitive advantages in bloom formation and dominance establishment. Studies have been conducted on the vertical migration patterns of Microcystis since the 1970s; however, bloom simulations remain limited. Here, we used a simple model based on the viscous drag force of turbulence and analysed the motion characteristics of Microcystis colonies. The vertical distribution of turbulent kinetic energy (K), cell concentration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Although direct measurements of turbulent kinetic energy were not recorded, these results corroborate the findings of Zhu et al. (2018), who demonstrated that Microcystis colonies tend to aggregate at depths where the turbulent kinetic energy of the surrounding water is approximately equal to the critical vertical turbulent kinetic energy of the colony under steady conditions and only exhibited diurnal migration under similar conditions. With real world applications in mind, however, measuring water temperature profiles is more practical than measuring turbulence levels of the water column.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Although direct measurements of turbulent kinetic energy were not recorded, these results corroborate the findings of Zhu et al. (2018), who demonstrated that Microcystis colonies tend to aggregate at depths where the turbulent kinetic energy of the surrounding water is approximately equal to the critical vertical turbulent kinetic energy of the colony under steady conditions and only exhibited diurnal migration under similar conditions. With real world applications in mind, however, measuring water temperature profiles is more practical than measuring turbulence levels of the water column.…”
Section: Discussionsupporting
confidence: 88%
“…Does the subsurface peak disperse and form a uniform algae profile, or does it form a surface bloom? Although vertical heterogeneity has been qualitatively correlated to subsequent surface bloom formation, there is a lack of quantitative modeling to support this observation (Liu et al., 2019; Xiao et al., 2018; Zhu et al., 2018). While it is beyond the scope of this paper to make definitive claims on the topic, some observations from this data set could orient future work in the right direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The buoyant velocity of cells is then calculated through a modified Stokes settling velocity that is governed by the difference between algal cell density and the surrounding water density (Wallace et al, 2000 ). Turbulent transport has since been incorporated into these models (Medrano et al, 2013 ; Zhu et al, 2018 ). By combining their model with principal component analysis, Feng et al ( 2018 ) demonstrated that turbulence‐induced mixing explained over half of the variability of early surface bloom formation, and that buoyancy regulation was more important for bloom maintenance and formation of late‐season blooms.…”
Section: Introductionmentioning
confidence: 99%